First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae) - Jiang, Xuan-Kong; Guo, Xuan; Yu, Zhi-Gang; Chen, Hui-Ming (Zootaxa, 2017)
Spiders of the subfamily Coelotinae prefer moist and dark places, such as cliffs, logs, stones, bark, leaf litter, corners, holes and crevices of buildings as well as caves (Wang 2002). As for species inhabiting caves, the majority are troglophilic and trogloxenic, but few ones being troglobitic (Liu & Li 2009). Five cave-dwelling eyeless members have been described up to date, all known only from females. Coelotes troglocaecus Shimojanal & Nishihira, 2000 was recorded from Okinawa Island, Japan, and four others from China: Draconarius yosiianus (Nishikawa 1999) from Guangxi Province; D. tortus Chen, Zhu & Kim 2008, D. proximus Chen, Zhu & Kim 2008 and D. digituliscaput Chen, Zhu & Kim 2008 from Guizhou Province (Nishikawa 1999, Chen et al. 2008).